Designing Anonymous Signature-Based Authenticated Key Exchange Scheme for Internet of Things-Enabled Smart Grid Systems - Srinivas, Jangirala; Das, Ashok Kumar; Li, Xiong; Khan, Muhammad Khurram; Jo, Minho (IEEE transactions on industrial informatics, 2021)
Recent technological evolution in the Internet of Things (IoT) age supports better solutions to magnify the management of the power quality and reliability concerns, and imposes the measures of a smart grid. In smart grid environment, a smart meter needs to securely access the services from a service provider via insecure channel. However, since the communication is via public channel, it imposes various security threats by an adversary. To deal with this, in this article we design a new anonymous signature-based authenticated key exchange scheme for IoT-enabled smart grid environment, called AAS-IoTSG. The dynamic smart meter addition phase is also permissible in AAS-IoTSG after initial deployment. The security of AAS-IoTSG has been tested rigorously using formal security analysis under the real-or-random (ROR) model which is one of the broadly-accepted standard random oracle models, formal security verification under the broadly-used automated validation of Internet security protocols and applications (AVISPA) tool and also using informal security analysis. Finally, an exhaustive comparative study unveils that AAS-IoTSG supports better security and functionality features and requires less communication and computation overheads as compared to the existing state-of-art authentication mechanisms in smart grid systems.